Probing displaced top quark signature at the LHC Run 3 - Jeremy Andrea; Daniel Bloch; Éric Conte; Douja Darej; Robin Ducrocq; Emery Nibigira (European Physical Journal C: Particles and Fields, 2023)
Abstract In the context of prospective studies for searches of new physics at the LHC Run 3, this paper investigates the relevance of using top quarks produced from new long-lived particles, and detected in the tracker volume of the ATLAS and CMS experiments. Such a signature, referred to as displaced top quarks, leads to final states containing displaced vertices and a high multiplicity of displaced jets and tracks, thanks to the top quark decays. Therefore, it is a possible powerful tool for searching for new long-lived particles. Three simplified models based on supersymmetry are explicitly designed for the study of this signature. They differ according to the nature of the long-lived heavy particle which produces at least one top quark: electrically neutral or charged, coloured or non-coloured long-lived particle. For each model, a wide region of parameter space, consistent with a reasonable number of displaced top quarks decaying in a typical tracker volume has been probed. From this study, promising benchmarks are defined and experimental guidelines are suggested.